KARAKTERISTIK SOSIODEMOGRAFI REMAJA DAN DEWASA MUDA DENGAN IDE BUNUH DIRI SERIUS PADA MASA PANDEMI - Pandia, Veranita; Danasasmita, Febrianti (PERDOSNI, 2025)
ABSTRACT Introduction: The incidence of suicide among adolescents and young adults is on the rise, including in Indonesia. COVID-19 pandemic has created a global crisis situation, increasing the risk of individuals contemplating ending their lives. Sociodemographic characteristics of adolescents and young adults are important factors to consider in relation to their vulnerability to suicidal ideation. Aim: This study aims to examine the correlation between sociodemographic characteristics and serious suicidal ideation among adolescents and young adults. Methods: This research employed a cross-sectional study involving 1,508 high school students and 526 university students in Bandung and its surrounding areas. Participants completed a questionnaire on sociodemographic characteristics and the Suicide Ideation Scale (SIS) through online guidance (Zoom meeting). The research findings were analyzed using t-Test on variables consisting of 2 groups and ANOVA test for variables consisting of more than 2 groups followed by Tukey's HSD post-hoc test. Results: The study found that female (p<0.001), respondents' education as a student (p<0.05), parental education as a diploma and bachelor’s degree (p<0.05), and parental separation (p<0.001) were correlated with the presence of serious suicidal ideation among both adolescents and young adults. Discussion: Sociodemographic characteristics correlating with serious suicidal ideation were gender, respondents' education level, parental education level, and parental marital status. Further research is needed to understand various suicide risk factors in adolescents and young adults in Indonesia, including biological, psychosocial, and cultural factors. Keywords: adolescents, sociodemographic, suicidal ideation, young adults